Given that cos 2 θ = 4 1 + 5 , if tan 2 ( 3 θ ) tan 2 ( θ ) is equal to n m , where m and n are coprime positive integers, find m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice approach. Up voted. A little shortening using componando-dividendo. 1 + t 2 1 − t 2 = 4 1 + 5 , ⟹ 2 1 − t 2 = 5 ∗ ( 1 + 5 ) 1 + 5 = 5 5 . ⟹ t 2 = 1 − 5 2 . ∴ T a n 2 ( 3 θ ) ∗ T a n 2 θ = ( 1 − 3 t 2 t ( 3 − t 2 ) ) 2 t 2 = { 1 − 3 t 2 t 2 ( 3 − t 2 ) } 2 { 2 ∗ ( − 1 + 5 3 ) ( 1 − 5 2 ) 2 ∗ ( 1 + 5 1 ) } 2 = { 5 1 ∗ 5 − 3 ( 5 − 2 ) ( 5 + 1 ) } 2 = { 5 1 ∗ 5 − 3 3 − 5 } 2 . T a n 2 ( 3 θ ) ∗ T a n 2 θ = 5 1 . m + n = 6
Recall: cos ( θ 1 + θ 2 ) = cos θ 1 cos θ 2 − sin θ 1 sin θ 2 and cos ( θ 1 − θ 2 ) = cos θ 1 cos θ 2 + sin θ 1 sin θ 2 Thus we have: tan 2 ( 3 θ ) tan 2 ( θ ) = ( cos 3 θ cos θ sin 3 θ sin θ ) 2
sin 3 θ sin θ = sin 3 θ sin θ − sin 3 θ sin θ + cos 3 θ cos θ − cos 3 θ cos θ + sin 3 θ sin θ
2 sin 3 θ sin θ = sin 3 θ sin θ − sin 3 θ sin θ + cos 3 θ cos θ − cos 3 θ cos θ
sin 3 θ sin θ = 2 ( cos 3 θ cos θ + sin 3 θ sin θ ) − ( cos 3 θ cos θ + sin 3 θ sin θ )
sin 3 θ sin θ = 2 1 ( cos ( 3 θ − θ ) ) − cos ( 3 θ + θ ) ) = 2 1 ( cos 2 θ − cos 4 θ )
We can transform the cosine terms in a similar fashion and we get:
cos 3 θ cos θ = 2 1 ( cos 2 θ + cos 4 θ )
Thus our combined expression looks as follows:
tan 2 ( 3 θ ) tan 2 ( θ ) = ( cos 2 θ + cos 4 θ cos 2 θ − cos 4 θ ) 2
Recall: cos 4 θ = cos 2 2 θ − sin 2 θ = 2 cos 2 2 θ − 1
Therefore our above expression can be simplified as follows:
( cos 2 θ + cos 4 θ cos 2 θ − cos 4 θ ) 2 = ( cos 2 θ + ( 2 cos 2 2 θ − 1 ) cos 2 θ − ( 2 cos 2 2 θ − 1 ) ) 2 = ( cos 2 θ + 2 cos 2 2 θ − 1 cos 2 θ − 2 cos 2 2 θ + 1 ) 2 cos 2 2 θ = ( 4 1 ) 2 ( 1 + 5 ) 2 = 1 6 6 + 2 5 = 8 3 + 5
( 4 1 ( 1 + 5 ) + 8 2 ( 3 + 5 ) − 1 4 1 ( 1 + 5 ) − 8 2 ( 3 + 5 ) + 1 ) 2 = ( 4 4 + 2 5 − 4 − 4 2 + 1 ) 2 = ( 5 1 ) 2 = 5 1
Thus m = 1 , n = 5 and m + n = 6
I think there is some typo in lines 2-5. Please check.
The fraction at the end of the second last line should be 5 1 n o t 6 1 .
Given : cos 2 θ = 4 1 + 5 = 2 ϕ with ϕ = 2 1 + 5 being the "golden ratio"
then θ = 1 0 π is a solution which leads to tan 2 ( 3 θ ) tan 2 ( θ ) = . 2
and . 2 = 5 1 with 1 + 5 = 6 which was the answer sought.
Another Fun Fact ! : cos ( 5 π ) = 2 ϕ
How did you go from "then θ = 1 0 π is a solution" to "which leads to tan 2 ( 3 θ ) tan 2 ( θ ) = . 2 "?
Nice way of looking at the problem. Up voted.
How did you go from "then θ = 1 0 π is a solution" to "which leads to tan 2 ( 3 θ ) tan 2 ( θ ) = . 2 "?
Log in to reply
I used direct substitution: t a n 2 ( . 3 π ) ∗ t a n 2 ( . 1 π ) = . 2 using a TI84+ calculator.
C o s 2 X = 2 C o s 2 X + 1 = 2 4 1 + 5 + 1 = 8 5 + 5 S i n 2 X = 1 − C o s 2 X = 8 3 − 5 S i n 3 X = 3 S i n X − 4 S i n 3 X , C o s 3 X = − 3 C o s X + 4 C o s 3 X ∴ T a n 3 X ∗ T a n X = − 3 C o s X + 4 C o s 3 X 3 S i n X − 4 S i n 3 X ∗ C o s X S i n X = C o s 2 X S i n 2 X ∗ − 3 + 4 C o s 2 X 3 − 4 S i n 2 X = 8 5 + 5 8 3 − 5 ∗ − 3 + 4 8 5 + 5 3 − 4 8 3 − 5 = ( 5 + 5 ) ( 3 − 5 ) ∗ − 6 + 5 + 5 6 − ( 3 − 5 ) = 5 ∗ ( 5 + 1 ) ∗ ( − 1 + 5 ) 9 − 4 = 4 ∗ 5 4 . ∴ T a n 2 3 X ∗ T a n 2 X = 5 1 . ⟹ m + n = 6
Your componendo and dividendo solution is the best! KUDOS!!
hahahaha, I used my Calculator nad found that theta = 18
the original problem stated everything in numbers instead of theta. I just changed it because I did not want to write out the numbers.
Fun fact: The solution to tan ( 3 θ ) tan ( θ ) which in the context of this problem is 5 1 is actually a = 2 ϕ − 1 1 where ϕ is the golden ratio, a very important and beautiful constant in nature. Just thought it was really cool that such a connection existed
expression=tan^2(t).tan^2(3t). =1÷(cot^2 (t).cot^2(3t))=m\n. m=1,n=cot^2 (t)+cot^2 (3t). cos(2t)=1+√5\4. So 2cos^2(t)=5+√5\4. cos ^2(t)=5+√5\8 so sin^2(t)=3-√5\8. cos3t=cos2t.cos t-sin2t.sint. =cos t(cos2t-2sin^2(t)). cos ^2(3t)=cos^2(t).((2cos^2(t)-1)-2+2cos^2(t)) ^2. cos^2(t).(4cos^2(t)-3)^2. =(5+√5)\8×(4×(5+√5)\8-3)^2=5-√5\8. so sin^2 (3t)=3-√5\8. n=((5+√5)÷8) ×(8÷(3-√5)×((5-√5)÷8)×(8÷(3-√5)) n=(5-√5).(5+√5)(3-√5).(3+√5)=20÷4=5. m+n=1+5=6#####
Problem Loading...
Note Loading...
Set Loading...
Let t = tan θ , then using the half-angle identity of cosine, we have:
cos ( 2 θ ) ⇒ 1 + t 2 1 − t 2 4 − 4 t 2 ( 5 + 5 ) t 2 ⇒ t 2 = 1 + tan 2 θ 1 − tan 2 θ = 4 1 + 5 = 1 + 5 + ( 1 + 5 ) t 2 = 3 − 5 = 5 + 5 3 − 5 = 2 5 − 5 ( 3 − 5 ) ( 5 − 5 ) = 2 0 2 0 − 8 5 = 5 5 − 2
tan 2 ( 3 θ ) tan 2 θ = ( 1 − 3 t 2 t ( 3 − t 2 ) ) 2 t 2 = ( 1 − 3 t 2 ) 2 t 4 ( 3 − t 2 ) 2 = ( 5 ( 6 − 2 5 ) ( 5 − 2 ) ( 2 5 + 2 ) ) 2 = ( 5 ( 3 − 5 ) ( 5 − 2 ) ( 5 + 1 ) ) 2 = ( 5 ( 3 − 5 ) 3 − 5 ) 2 = 5 1
⇒ m + n = 1 + 5 = 6